Efficacy of Scalp Acupuncture in Patients With Post-stroke Hemiparesis: Meta-Analysis of Randomized Controlled Trials - Huang, Yuan-Ju; Huang, Chih-Shan; Leng, Kuo-Feng; Sung, Jia-Ying; Cheng, Sheng-Wei (Frontiers in Neurology, 2021)
Objectives: To conduct a meta-analysis to assess the efficacy of scalp acupuncture (SA) in patients with stroke and consequent hemiparesis regardless of brain infarction or intracerebral hemorrhage. Methods: A literature search of randomized controlled trials (RCTs) on scalp acupuncture for stroke was performed in five databases up to May 10, 2021. We investigated three types of outcome: motor function, sequelae of poststroke hemiparesis, and adverse effects. Methodological quality was assessed using the revised Cochrane risk of bias tool version 2.0. Results: Of 1063 papers, 30 RCTs involving Fugl–Meyer Assessment were selected, among which 10 and 4 RCTs were selected for evaluation of courses lasting of 1 and 3 months, respectively. The meta-analysis of 1- and 3-month courses revealed significant differences in the motor function of the SA plus western standard treatment group versus western standard treatment only (medication plus rehabilitation; P < 0.001). A 3-month course tended to result in better outcomes than a 1-month course. Conclusions: Our meta-analysis results reveal that SA improves motor function in patients with acute to chronic stroke, regardless of brain infarction or intracerebral hemorrhage. However, because of a lack of methodological quality, thoroughly planned clinical studies are still required.